A 2D water-stable metal–organic framework for fluorescent detection of nitroaromatics. (15th November 2018) - Ning, Shigang; Chen, Hongjuan; Zhang, Shaowei; Cheng, Peng
Graphical abstract: A 2D water-stable MOF has been prepared and characterized by various tools, which can sensitively and selectively detect Cr2 O7 2− /CrO4 2− and nitroaromatics in aqueous solution. Abstract: By reacting Zn(NO3 )2 ·6H2 O and H2 btca in the presence of iqo under hydrothermal conditions to give a 2D water-stable metal–organic framework (MOF), [Zn(btca)(iqo)2 ] n (1 ) (H2 btca = benzotriazole-5-carboxylic acid, iqo = isoquinoline), which has been verified by combining X-ray single-crystal diffraction, thermogravimetric (TG) analysis, and infrared (IR) spectrum. Each five-coordinated Zn 2+ in1 exhibits a pentagonal bipyramid geometry defined by four N atoms from two btca 2− ligands and two iqo molecules, and one O atom from one carboxylate group of btca 2− ligand. Neighbouring Zn 2+ are bridged by btca 2− ligands to form a 2D 'fes '-type network, further generating a 3D supramolecular network through hydrogen bonds and π ⋯ π stacking interactions. Importantly, MOF1 exhibits strong fluorescence in aqueous solution and can be used for detecting Cr2 O7 2− /CrO4 2− and nitroaromatics compounds based on fluorescence quenching effects. Furthermore, experimental and theoretical calculations suggest that the fluorescence quenching effect could be mainly ascribed to the electron and energy transfer as well as electrostatic interactions between1 and nitroaromatics analytes.